(3GdEjVGMs - (3Ydj Hf eMeO Hf YHO Gddg GdeJWHH GdCaRQjs ((3SjO Ydj GdWHGWHGFj s)
(3ChdgG (B:s
(3GdMeO ddg cJHJ cJGHkG hGVMkG aj GdWH djfJaY Hg GdeSdehf hSejJg GdEjVGM hQJHJg Ydi ebOeI hebGdJjf s
(3BNQgG (B:s
(3hbO jbUO ef EUGHI VQHI Ch SbWI aj GdMGd Edi GdehGVY CdekG, hbO jVYagG s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B- (3GdehUd (B(1/131) s
Keywords: (3GdWHs